Targeting colorectal cancer with hesperidin and hesperetin: a comprehensive review of antiproliferative activity, chemopreventive, anti-inflammatory, and antioxidant effects - Qi, Ming; Su, Yu (Frontiers in Nutrition, 2025)
Colorectal cancer (CRC) residues one of the leading reasons of cancer-related mortality worldwide, with increasing incidence attributed to dietary, environmental, and genetic factors. Despite advances in conventional therapies, including chemotherapy and targeted agents, treatment resistance and adverse side effects highlight the need for novel, safer, and more effective therapeutic strategies. Hesperidin (HSD) and hesperetin (HST), bioflavonoid abundantly found in citrus fruits, has emerged as a promising candidate due to its wide-ranging biological activities, particularly its role in modulating key molecular pathways involved in carcinogenesis. This comprehensive review explores the multifaceted anticancer potential of HSD and HST in the context of CRC, focusing on its ability to control programmed cell death mechanisms like autophagy and apoptosis, suppress chronic inflammation, and counteract oxidative stress—three pivotal hallmarks of tumor initiation and progression. Additionally, we examine the synergistic effects of HSD and HST with standard chemotherapeutic agents and its potential as a chemopreventive or adjuvant therapeutic compound. By consolidating preclinical and emerging clinical evidence, this review highlights the translational value of HSD and HST in CRC prevention and management. Understanding its molecular underpinnings may pave the way for HSD- and HST-based nutraceuticals and targeted therapies, contributing to a more personalized and integrative approach to CRC treatment.